Radial Growth in 2D Revisited: The Effect of Finite Density, Binding Affinity, Reaction Rates, and Diffusion. Issue 1 (10th October 2016) - Bihr, Timo; Sadafi, Fabrizio‐Zagros; Seifert, Udo; Taylor, Robin Klupp; Smith, Ana‐Sunčana
Abstract : Dendrite growth of metal patches on colloidal particles shows a variety of structures depending on the preparation conditions. The morphology of these patches suggests a cross‐over from a reaction to a diffusion limited growth, implicating diffusion on the particle surface. Interestingly, the morphological and optical characteristics of the patches continuously change between two limiting behaviors. To understand this growth process, extensive simulations are performed, studying the fractal dimension and the dynamics of growth of a patch on a particle of a finite size, as a function of the initial density and the binding affinity of diffusing tracers. Several important growth regimes are characterized that enable to optimize the pathway for the synthesis of optically active, patchy particles. Abstract : Fractal dimensions and growth exponents for dendrite developing on enclosed surfaces are studied as a function of experimentally relevant parameters building a complex phase space of morphologies. These results allow us to predict the morphology of domains building Janus particles.